Efektivitas Unclos Ditinjau Dari Kasus Illegal Fishing Di Laut Natuna (2012-2021) - Maf'ullilahi Zakinah; Widia Grace Tayan; Axel Davina Zahra Kusuma; Raden Roro Inori Athalia Noreendra; Ayunda Adis Rizkia; Lucitania Rizky (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2024)
The Natuna Sea is one of Indonesia's territorial waters that borders many countries so that it is often an easy target for illegal fishing, including ships belonging to China, Vietnam and Thailand.  Not only does it harm the country's economy and local fishermen, but illegal fishing also causes damage to marine ecosystems and coral reefs, even though Indonesia as a country that ratified the United Nations Convention on the Law of the Sea or commonly referred to as UNCLOS has adopted rules governing this in its law. Using the Base on research method that we collected from various journals, websites, electronic scientific articles and other research reports, we attempt to (1) analyse the effectiveness of UNCLOS in addressing maritime issues such as illegal fishing (2) to determine the compliance of UNCLOS ratifying countries involved in illegal fishing cases in the Natuna Sea seen from green politics theory and Robert B. Mitchell's compliance theory. Mitchell's compliance theory.  The results we found are that the entry of ships belonging to China, Vietnam and Thailand into the Natuna Sea shows the ineffectiveness of UNCLOS and the lack of compliance of the ratifying countries.